Evaluating policy coherence in food, land, and water systems: evidence from India - Council on Energy, Environment and Water (CEEW); International Water Management Institute (International Water Management Institute (IWMI). CGIAR Initiative on National Policies and Strategies, 2023)
The critical interlinkages among the food, land, and water (FLW) systems are complex and context-specific. There has been limited research on how policies governing one resource have deep implications for the other linked resources. Further, the process of developing policies is highly complex, and each evolves differently. In addition, policy changes are implemented in response to socio-cultural, economic, environmental, and political changes. Thus, individual policies may develop conflicting priorities and effects. To ensure the effectiveness of national policies and strategies, it is crucial to gather context-specific evidence on the coherence between policies governing FLW systems and address points of incoherence. Policy coherence is important to identify and strengthen synergies across economic, social, and environmental policy areas and address any trade-offs1 between them to align domestic policy objectives with internationally agreed objectives. The study offers key evidence-based recommendations to address the identified gaps and challenges in the selected national policies, which are essential for enhancing policy coherence.